2022-VA-1522-ESGO New Keystone flap application in vulvo-perineal reconstructive surgery for vulvar cancer. (20th October 2022) - Altieri, Alfonso; Fais, Giuseppina; Carboni, Giulia; Deo, Giuseppe; Fais, Maria Luisa; Ungredda, Andrea; Figus, Andrea; Mais, Valerio; Angioni, Stefano; Peiretti, Michele
Abstract : Introduction/Background: This report aimed to illustrate the video-guided application of the Keystone perforator island flaps (KPIF) technique in a patient with diagnosis of vulvar cancer. Methodology: Eight patients were selected for the study: seven of them underwent radical vulvectomy for vulvar squamous cell carcinoma (SCC), and one underwent vulvar wide excision for Paget disease. The Keystone perforator island flaps technique was adopted for all these vulvar reconstruction. The team approach comprised both a gynecologic oncologist and a plastic surgeon in all procedures. The defects were successfully covered by the Keystone flap technique in all patients. Results: Bilateral Keystone flaps were taken from the medial and proximal region of the thigs, with incision lines coinciding with the natural skin folds. When flaps vitality was determined, each one was positioned along the perineal midline for labia majora and vaginal opening reconstruction. Final reconstructive step coincided with skin and vaginal mucosa suture. No post-operative short complications in the described case were observed. Conclusion: The Keystone technique is an extremely simple and effective solution, easily applicable and reproducible. KPIF technique warrants an excellent vascular supply and does not require delicate perforator dissection. Additionally, it is associated with minimal morbidity in donor sites, a lower risk of flap necrosis and lower intraoperative and postoperative complications. Keystone flap method also yields good aesthetic and functional results by preserving shape and contour, avoiding differences in skin coloration and preserving sensitivity with an excellent cosmetic outcome in terms of patient satisfaction and postoperative scars and with an acceptable complication rate. Further studies with larger sample size are required to evaluate the efficacy of this technique.